(untitled) - Hirschey, Mark (London, 1993)
The book provides a solid foundation of economic understanding for use in managerial decision making. It offers an intuitive calculus-based treatment of economic theory and analysis. A wide variety of examples and simple numerical problems illustrate the application of managerial economics to a wide variety of practical situations. The nature of the decision process and the role that economic analysis plays in that process are emphasized throughout the text. Although both micro- and macroeconomic relations have implications for managerial decision making, the book concentrates on microeconomic of particular importance. Following the development of the economic model of the firm, the vital role of profits is examined. The book explores production theory, cost analysis, and linear programming techniques as means for understanding the economics of resource allocation and employment. It also provides a foundation for studying the external economic environment and for examining the pricing practices requied for successful management. The role of government in the market economy, including the constraints it imposes on management, requires an examination of regulation and antitrust law. Finally, capital budgeting is shown as the method for introducing marginal analysis into the long-range strategic planning and control process
Keywords: Managerial economics